Toxic Relationships: The Unbearable Tension Between Stabilization Clauses, State Sovereignty and Human Rights under International Law - Núñez del Prado, Fabio (2020)
Large-scale investments depend on various economic, natural and social factors of the State where they invest. Also, from an economic point of view, once the investment has been made, the financial viability of the project depends, to a large extent, on the investor’s ability to capture cash flows. However, investors will always be at some degree of risk.In this article, the authors examine whether Stabilization Clauses, a widely used risk management device in investment contracts, can affect a State’s action in implementing its international human rights and environmental obligations. Specifically, they assess whether Stabilisation Clauses can limit the application and creation of new social or environmental regulations to investment activities during the life of the investment.